Chlorpheniramine, an Old Drug with New Potential Clinical Applications: A Comprehensive Review of the Literature - Rizvi, Syed A.A.; Ferrer, Gustavo; Khawaja, Uzzam A.; Sanchez-Gonzalez, Marcos A. (Current Reviews in Clinical and Experimental Pharmacology, 2024)
Chlorpheniramine Maleate (CPM), also known as chlorphenamine, is a potent alkylamine first-generation H1 antihistamine that has been used since the 1950s. CPM is a widely popular drug commonly used to treat allergic conditions, given its antihistamine properties. Although mainly used in over-the-counter treatment for cough and colds, various studies discuss a wide range of CPM's clinical uses, such as treating asthma, plasma cell gingivitis, chronic urticaria, and depression, among others. This antihistamine is usually taken orally; however, intravenous, intramuscular, and subcutaneous routes have been documented. Intranasal routes of this drug have recently been explored, especially due to its antiviral properties against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Accordingly, given CPM's extensive medical and safety profile, the present review explores this versatile drug's current and potential clinical applications. Although it is widely used mainly for treating common colds and aforementioned allergic conditions, CPM can be used for other clinical indications. The repurposing of CPM for other clinical indications, such as COVID-19, needs to be further explored through more extensive studies.
Keywords: rhinitis